SALL4 positive fetal gut‐like adenocarcinoma of the duodenum. (27th October 2014) - Kinoshita, Shoichi; Sho, Masayuki; Enomoto, Yasunori; Koyama, Fumikazu; Akahori, Takahiro; Nagai, Minako; Ito, Masahiro; Morita, Kohei; Ohbayashi, Chiho; Nakajima, Yoshiyuki
<x xml:space="preserve">Abstract</x> Fetal gut‐like adenocarcinoma is a rare carcinoma, previously reported in the stomach, which features clear cytoplasm cell papillotubular carcinoma and morphology similar to the fetal gut epithelium. SALL4, a novel marker for progenitor‐type tumors, has shown high expression in fetal gut‐like adenocarcinoma, which may represent oncofetal protein expression and fetal differentiation. Herein, we report the first case of fetal gut‐like adenocarcinoma of the duodenum. An 81‐year‐old man was admitted on account of jaundice. A deeply ulcerating duodenal tumor formed a 4 cm periampullar mass. Pancreatoduodenectomy with lymphadenectomy was performed. Funicular and solid growth of clear cytoplasmic cells that resembled the fetal gut epithelium formed a poorly differentiated adenocarcinoma. Lymph node metastasis was present. Immunohistochemistry analysis showed diffuse nuclear positivity for SALL4. For postoperative therapy, S‐1 was administered. The patient is alive with no recurrence, 83 months postoperatively. This case may contribute to further elucidate the disease entity of SALL4 positive, fetal‐type carcinomas.